2017
DOI: 10.5114/biolsport.2017.69826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of order and sequence of resistance and endurance training on body fat in elementary school-aged girls

Abstract: The purpose of this study was to analyse the effects of order and sequence of concurrent resistance and endurance training on body fat percentage (BFP) in a large sample of elementary school-aged girls. One hundred and twenty-six healthy girls, aged 10-11 years (10.95 ± 0.48 years), were randomly assigned to six groups to perform different training protocols per week for 8 weeks: Resistance-only (R), Endurance-only (E), Concurrent Distinct Endurance-Resistance (CDER), Concurrent Parallel Endurance-Resistance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our results are consistent with results of previous studies (Greening et al 2011, Vanhelst et al 2011, that showed better results on physical fitness values and decreases on body composition values in experimental group constituted by obese students (9months physical activity program, 2 sessions/week), or even was observed significant differences on body mass index (BMI), with decreases in experimental group and increases in control group, after a 12 months long physical activity program. the results of the current study are also congruent with results of a previous study (Alves et al 2017) in this area which were showed significantly decreases on body fat percentage in experimental group constituted by prepubescent girls (8-week concurrent training, 2 sessions/week). Dorgo et al (2009) verified the effectiveness of different physical training programs on physical fitness levels, however did not observed differences on body composition values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with results of previous studies (Greening et al 2011, Vanhelst et al 2011, that showed better results on physical fitness values and decreases on body composition values in experimental group constituted by obese students (9months physical activity program, 2 sessions/week), or even was observed significant differences on body mass index (BMI), with decreases in experimental group and increases in control group, after a 12 months long physical activity program. the results of the current study are also congruent with results of a previous study (Alves et al 2017) in this area which were showed significantly decreases on body fat percentage in experimental group constituted by prepubescent girls (8-week concurrent training, 2 sessions/week). Dorgo et al (2009) verified the effectiveness of different physical training programs on physical fitness levels, however did not observed differences on body composition values.…”
Section: Discussionsupporting
confidence: 92%
“…literature agrees that low-to moderate-intensity resistance should be conducted 2-3 times/week on non-consecutive days (Behm et al 2017, Hass et al 2001 but several studies had been focused in one frequency, did not compared different frequencies (Alves et al 2017, Greening et al 2011. To the best of our knowledge, there is a lack of evidences about the effects of different training program frequencies back saver sit-and-reach left; Sit and Reach Right: back saver sit-and-reach right; BMI: body mass index; BF: body fat percentage; G: group factor; Pre-Post: momentum factor; G * Factor: interaction between factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all anthropometric measures showed no statistically significant changes in the present study. However, there was a study [52] reporting different results. The authors showed significant decreases in body fat in all experimental groups (including concurrent training groups) in prepubescent children [52].…”
Section: Twelve Weeks Of Reduced Training and Detrainingmentioning
confidence: 99%
“…However, there was a study [52] reporting different results. The authors showed significant decreases in body fat in all experimental groups (including concurrent training groups) in prepubescent children [52]. One possible explanation may be attributed to the children in all groups experiencing biological maturation and physical growth at the same time [9].…”
Section: Twelve Weeks Of Reduced Training and Detrainingmentioning
confidence: 99%
“…A total of 3,486 participants (1,685 girls) were included in the control group (CON) group that participated in regular physical activity (PA) or physical education (PE), 426 participants (171 girls) were included in the active video games (AVGs) group (24-31), 1,670 participants (803 girls) were included in the game-based exercise (GB) group (32-42), 1,085 participants (522 girls) were included in the high-intensity interval training (HIIT) group (36, 37, 43-65), 1,005 participants (462 girls) were included in the strength training (ST) group (41,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82), 599 participants (300 girls) were included in the aerobic training (AT) group (49,53,56,61,62,66,76,(83)(84)(85)(86)(87), and 307 participants (197 girls) were included in the combined aerobic and strength training (CT) group (68-71, 76, 88, 89). Interventions lasted on average of 13.9 ± 9.6 weeks and ranged from 4 to 50 weeks, with 73% of studies lasting less than 12 weeks.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%